Religion and academia reframed: connecting religion, science, and society in the Long Sixties - Rota, Andrea (Method & theory in the study of religion / Supplements, 2023)
"The Long Sixties (1955-1973) were a period of economic prosperity, political unrest, sexual liberation, cultural experimentation, and profound religious innovation throughout the Western world. This social effervescence also affected the study of religion by reshaping the relationships between academic and religious institutions and discourses. While the mainstream churches sought to deploy the instruments of the social sciences to understand and manage the changing socioreligious context, prominent scholars regarded the bubbly spirituality of the counterculture as the harbinger of a new era; some of them actively used their academic knowledge to further this revolution. This book discusses the multiple entanglements of religion and science during these turbulent decades through theoretically informed case studies from both sides of the Atlantic"--